Cryptomarkets and the returns to criminal experience - Ouellet, Marie (Global crime, 2022)
Criminal capital theory suggests more experienced offenders receive higher returns from crime. Offenders who accrue skills over their criminal career are better able to minimise detection, increase profits, and navigate illegal markets. Yet shifts in the offending landscape to technologically-dependent crimes have led some to suggest that the skills necessary to be successful in conventional crimes no longer apply, meaning ‘traditional’ criminals may be left behind. The recent turn of drug vendors to online markets provides an opportunity to investigate whether ‘street smarts’ translate to success in technologically-dependent crimes. This study surveys 51 drug vendors on online drug markets to compare individuals who began their drug-selling career in physical drug markets with vendors whose onset began on digital platforms. The findings suggest vendors who broker between online and offline drug markets are better positioned to maximize profits. The results inform potential spillover effects from offline drug-selling into online marketplaces.